An experimental reproduction of necrotic enteritis In broiler chickens - Redondo, Leandro Martín; Redondo, Enzo Alejandro; Delgado, Fernando Oscar; La Sala, Luciano Francisco; Fernandez Miyakawa, Mariano Enrique (2017)
Clostridium perfringens is the main causative agent of avian necrotic enteritis (NE), an enteric infectious disease considered among the most important diseases in the poultry industry. Currently, there are numerous reports of experimental reproduction of NE using different inoculation protocols along with various predisposing factors which produce highly variable results. These models represent a fraction of a wide range of farming conditions under which disease can develop. This work describes the experimental induction of C. perfringens NE in broiler chickens after a short feed withdrawal of 12 hours prior to bacterial challenge. Broiler chicks fed with commercial chick starter for 14 days post-hatch were afterwards offered feed mixed with C. perfringens twice a day for three consecutive days. On average, over 60% of challenged birds developed typical gross lesions. The results show that it is possible to reproduce the disease under conditions similar to those found in poultry farms which are not covered by other developed models. This model proved to be effective in the experimental reproduction of NE, allowing the evaluation of pathological parameters.